Black fungus gnat – An invasive pest of French bean in Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2023)
French bean is an important vegetable in most tropical and subtropical countries and is a food source for humans and animals. A survey was carried out on the Patuakhali Science and Technology University (PSTU) campus, Narsingdi, Sylhet, Hobigonj, and Mowlovibazar districts of Bangladesh to know the incidence pattern of insect pests of French bean from November 2016 to January 2017. Field screening of nine French bean varieties against major insect pests was conducted in the Regional Horticulture Research Centre, BARI, Shibpur, Narsingdi, from November 2017 to January 2018. Seven varieties viz., BARI Jharsheem-1, BARI Jharsheem-2, BARI Jharsheem-3, Sylhet local- 4, Sylhet local-5, Sylhet local- 6 and Sylhet local-7 were used as study materials to evaluate against major insect pests of French bean under natural field condition. Results revealed that black fungus gnat was first noticed on 13th December, 2016 and the prevalence continued upto the 12th January, 2017. The highest incidence (21/plant) of black fungus gnat was found in Habiganj and the lowest (9/plant) was on the PSTU campus. The highest number of black fungus gnats were captured at 38 DAS (89/trap) and the lowest number (56/trap) of black fungus gnats were at 28 DAS using a yellow sticky trap. The variety BARI Jharshim-3 had the highest population of Black fungus gnats, which indicated that the variety was highly susceptible to Black fungus gnats, while Sylhet local-7 had the lowest population of black fungus gnats indicating least susceptible to Black fungus gnats. Among all tested varieties, none showed complete resistance against black fungus gnats.J. Asiat. Soc. Bangladesh, Sci. 49(1): 1-11, June 2023